2005
DOI: 10.1161/01.res.0000151846.19788.e0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in Ca 2+ Sensitivity of the Slowly Activating Delayed Rectifier K + Current in Cardiac Myocytes

Abstract: Abstract-SarcolemmalIn a previous article, we showed that I Ks enhancement by elevation of [Ca 2ϩ ] i was inhibited by a calmodulin (CaM) inhibitor, but not by an inhibitor of CaM-dependent kinase II. 6 Although this finding suggests that the allosteric regulation of CaM is crucial for Ca 2ϩ -sensitive I Ks alterations, the detailed underlying mechanism remains unknown. Recently, we found that I Ks was enhanced by nitric oxide (NO) via a cGMP-independent mechanism. 7 Because allosteric interaction of Ca 2ϩ /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 30 publications
8
48
0
Order By: Relevance
“…The inhibition of I Ca,L by NO is caused by cGMP-dependent or cGMPindependent (direct S-nitrosylation/redox) pathways (17,19,20). Similarly, NO can modulate the delayed rectifier K ϩ currents by cGMP-dependent or -independent pathway (17,18,21). Interestingly, although CAPON overexpression activates NOS1-derived NO in our work, the electrophysiological changes mediated by this NO activation are comparable with those in previous reports (17)(18)(19)21).…”
Section: Reversal Of Capon Overexpression-induced Electrophysiologicalsupporting
confidence: 90%
See 2 more Smart Citations
“…The inhibition of I Ca,L by NO is caused by cGMP-dependent or cGMPindependent (direct S-nitrosylation/redox) pathways (17,19,20). Similarly, NO can modulate the delayed rectifier K ϩ currents by cGMP-dependent or -independent pathway (17,18,21). Interestingly, although CAPON overexpression activates NOS1-derived NO in our work, the electrophysiological changes mediated by this NO activation are comparable with those in previous reports (17)(18)(19)21).…”
Section: Reversal Of Capon Overexpression-induced Electrophysiologicalsupporting
confidence: 90%
“…Similarly, NO can modulate the delayed rectifier K ϩ currents by cGMP-dependent or -independent pathway (17,18,21). Interestingly, although CAPON overexpression activates NOS1-derived NO in our work, the electrophysiological changes mediated by this NO activation are comparable with those in previous reports (17)(18)(19)21). Recently, evidence emerged that NOS1 may play a critical role in the regulation of calcium handling and myocyte contraction in the heart (9,10,12,22).…”
Section: Reversal Of Capon Overexpression-induced Electrophysiologicalsupporting
confidence: 88%
See 1 more Smart Citation
“…It has also been demonstrated that NOS3 is able to modulate K ϩ channels. Specifically, activation of NOS3 leads to an enhancement of slowdelayed rectifier K ϩ current and shortening of APD in guinea pig myocytes (2). However, in normal adult mouse ventricular myocytes, the expression of delayed-rectifier K ϩ channel is very low (22), and the functional effects of I Ks on AP waveform are still undetermined (36).…”
Section: Nos3 and Arrhythmogenesismentioning
confidence: 99%
“…Moreover, testosterone increases by 30% the density of repolarizing potassium currents, which is due to changes in both gating kinetics of the delayed rectifier potassium currents (Ikr) and shortening the duration of the QT interval Testosterone has been shown to interact directly with the NO system. Activation of this pathway induces shortening in the duration of the action potential by activating the slow component of delayed rectifier potassium current (Iks) and inhibiting L-type calcium currents (Ica, L ) (Bai et al, 2004(Bai et al, , 2005.…”
Section: Effects Of Testosterone On Cardiac Excitabilitymentioning
confidence: 99%